Continuous year-round isolation of giant viruses from brackish shoreline soils - Akashi, Motohiro; Takemura, Masaharu; Suzuki, Seiichi (Frontiers in Microbiology, 2024)
Giant viruses, categorized under Nucleocytoviricota, are believed to exist ubiquitously in natural environments. However, comprehensive reports on isolated giant viruses remain scarce, with limited information available on unrecoverable strains, viral proliferation sites, and natural hosts. Previously, the author highlighted Pandoravirus hades, Pandoravirus persephone, and Mimivirus sp. styx, isolated from brackish water soil, as potential hotspots for giant virus multiplication. This study presents findings from nearly a year of monthly sampling within the same brackish water region after isolating the three aforementioned strains. This report details the recurrent isolation of a wide range of giant viruses. Each month, four soil samples were randomly collected from an approximately 5 × 10 m plot, comprising three soil samples and one water sample containing sediment from the riverbed. Acanthamoeba castellanii was used as a host for virus isolation. These efforts consistently yielded at least one viral species per month, culminating in a total of 55 giant virus isolates. The most frequently isolated species was Mimiviridae (24 isolates), followed by Marseilleviridae (23 isolates), Pandoravirus (6 isolates), and singular isolates of Pithovirus and Cedratvirus. Notably, viruses were not consistently isolated from any of the four samples every month, with certain sites yielding no viruses. Cluster analysis based on isolate numbers revealed that soil samples from May and water and sediment samples from January produced the highest number of viral strains. These findings underscore brackish coastal soil as a significant site for isolating numerous giant viruses, highlighting the non-uniform distribution along coastlines.